2019
DOI: 10.1002/smll.201903208
|View full text |Cite
|
Sign up to set email alerts
|

A Paclitaxel‐Based Mucoadhesive Nanogel with Multivalent Interactions for Cervical Cancer Therapy

Abstract: Cervical cancer treatment is subject to limited drug access to locally diseased targets and generally resistant to chemotherapy, thus it is essential to develop a local drug delivery system to overcome these problems, premised on guaranteeing drug efficacy. With this goal in mind, a multivalent interactions‐based mucoadhesive nanogel for vaginal delivery is proposed. Briefly, the nanogel is constructed with mucoadhesive poly(acrylic acid) as the backbone and multiple inclusions between β‐cyclodextrin and pacli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 45 publications
0
24
0
2
Order By: Relevance
“…However, other diseases, like those related to human papillomavirus, herpes simplex virus, and HIV, along with the unfortunate increase in the prevalence of cervix carcinoma, have recently driven the interest to develop vaginal formulations [ 134 ]. Several compelling investigations have shown that CDs are useful, as solubilizers, in the development of these type of formulations such as mucoadhesive gels, creams, and films for antifungal and antiviral activities [ [135] , [136] , [137] ]; gels for contraception purpose [ 138 ]; vaginal discs for the controlled delivery of antiretroviral drugs [ 139 ]; and mucoadhesive nanosystems for cervical cancer treatment [ 140 ]. Also studied are the mucoadhesive properties of CD derivatives in which CDs perse comprise the delivery systems [ 141 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, other diseases, like those related to human papillomavirus, herpes simplex virus, and HIV, along with the unfortunate increase in the prevalence of cervix carcinoma, have recently driven the interest to develop vaginal formulations [ 134 ]. Several compelling investigations have shown that CDs are useful, as solubilizers, in the development of these type of formulations such as mucoadhesive gels, creams, and films for antifungal and antiviral activities [ [135] , [136] , [137] ]; gels for contraception purpose [ 138 ]; vaginal discs for the controlled delivery of antiretroviral drugs [ 139 ]; and mucoadhesive nanosystems for cervical cancer treatment [ 140 ]. Also studied are the mucoadhesive properties of CD derivatives in which CDs perse comprise the delivery systems [ 141 ].…”
Section: Resultsmentioning
confidence: 99%
“…Not only did vaginal delivery of the nanogel show no side effects in an orthotopic cervical cancer model, but the retention time was also prolonged within the vagina, leading to more efficient tumor suppression. [105] Glaucoma is a neurodegenerative disease and the worldwide leading cause of visual impairment and blindness. Unfortunately, currently available drug formulations for its treatment have limited clinical applicability.…”
Section: (20 Of 38)mentioning
confidence: 99%
“…The pure organic nanogels can be prepared by crosslinking functional macromolecules, which are synthesized by modifying functional groups onto macromolecules ( Figure 1 a). The crosslinkers may have bi-functional or multi-functional groups, and the nanogels can be crosslinked via covalent bonds [ 48 ], supramolecular interactions [ 49 ], π–π stacking [ 50 ] and electrostatic interactions [ 51 ]. In addition, some crosslinkers contain environmentally responsive moieties such as disulfide bonds, endowing nanogels with responsiveness [ 52 ].…”
Section: Preparation Of Crosslinked Nanogelsmentioning
confidence: 99%
“…Compared with nanogels using conventional crosslinkers, drug-crosslinked nanogels showed unique advantages such as high drug loading content and improved drug release profile [ 81 ]. Zhu et al designed a paclitaxel (TAX)-crosslinked nanogels for cervical cancer therapy [ 49 ]. They first synthesized βCD- and TAX-grafted poly(acrylic acid) (PAA), giving PAA-βCD and PAA-TAX, respectively.…”
Section: Crosslinked Nanogels For Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation